Study on public awareness towards recycling activity in Kota Bharu, Kelantan Malaysia - Mohamed, Anuar; Abdul Rahman, Haliza (American-Eurasian Network for Scientific Information, 2014)
Background: The increase in the population had cause the production of solid waste to increase significantly. Rapidly changing lifestyle is the second factor that causes the production of waste at an alarming rate. Thus, recycling can be seen as one of the best alternatives to cope with the problem of solid waste management. Objective: This study aimed to identify the level of public knowledge and their practice of recycling in the town of Kota Bharu, Kelantan, Malaysia. In this study, a sample size of 384 respondents had been randomly selected. The respondents were residents of Kota Bharu, Kelantan, Malaysia and aged at least 18 years old. Respondents need to answer a set of questionnaire which given to them. The data was then analyzed using Statistical Package For Social Science (SPSS). This study managed to get 100% participation from respondents. Results: The outcome shows that there is significance relationship between demographic background and the knowledge, attitude and practice of recycling in Kota Bharu, Kelantan. However, only 31.8% of respondents practice recycling. Conclusion: In order to increase public participation and involvement in the recycling activity, they need to be educated on recycling continuously especially since they are young and the process of educating the next generation will be much easier. To achieve that, mass media is one of the best tools to convey the information on recycling to the public.